Coordinated operation of electricity and natural gas systems from day-ahead to real-time markets. (25th January 2021) - Guerra, Omar J.; Sergi, Brian; Craig, Michael; Pambour, Kwabena Addo; Brancucci, Carlo; Hodge, Bri-Mathias
Abstract: Power systems worldwide are becoming more reliant on energy from natural gas, wind, and solar, posing potential reliability and coordination challenges from the tighter coupling of these infrastructure systems. This paper proposes a framework for the market-based coordination of electricity and natural gas system operations. The proposed framework includes a power system model that accounts for flexibility in the commitment of power plants with short start-up and shut-down times, coupled with a dynamic gas model that simulates when gas cannot be delivered to generators. The capabilities of the framework are illustrated using real-world electric power and gas systems, including scenarios around wind and solar penetrations and the analysis of time-variant, "shaped flow" gas nominations. Our results indicate that coordination between power and gas systems improves total gas delivery and reduces out-of-merit order dispatch in the electricity system, and that shaped flows may reduce unserved gas in systems with high penetrations of wind and solar energy sources. Coordination can have mixed effects on carbon-dioxide emissions, with emissions increasing with coordination for current systems during high load weeks but decreasing for systems with high renewable penetrations, particularly during periods of high variability. Highlights: A framework for the coordination of electric power and gas systems is implemented. Coordination across three energy markets is evaluated. Coordination substantially reduces out-of-merit order dispatch in the electricity system. Shaped flows nominations may become increasingly valuable for reducing unserved gas.